Primer registro de Scolytus schevyrewi Semenov 1902 (Coleoptera: Curculionidae: Scolytinae) en México - Campos-Bolaños, Rodolfo; Atkinson, Thomas H.; Cibrian-Tovar, David; Méndez-Montiel, J. Tulio (Instituto de Ecología, A.C., 2015)
The first documented report for Scolytus schevyrewi Semenov (Curculionidae: Scolytinae), an exotic species of Mexico.